Theoretical Analysis of a Multi-Tier Supply Chain Management Process Integration: A Case Study Method - Muhammad Nauman Abbasi; Nadir Munir; Javaria Abbas (Sustainable Business and Society in Emerging Economies, 2022)
Purpose: - Case studies of 12 automotive supply chains are used to build a theory of multi-tier supply chain management (SCM) processes integration which links patterns of multi-tier process integration with cost and differentiation strategies of the focal firms.